2017
DOI: 10.1038/s41598-017-07383-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel animal model defines genetic contributions for neuron-to-neuron transfer of α-synuclein

Abstract: Cell-to-cell spreading of misfolded α-synuclein (α-syn) is suggested to contribute to the progression of neuropathology in Parkinson’s disease (PD). Compelling evidence supports the hypothesis that misfolded α-syn transmits from neuron-to-neuron and seeds aggregation of the protein in the recipient cells. Furthermore, α-syn frequently appears to propagate in the brains of PD patients following a stereotypic pattern consistent with progressive spreading along anatomical pathways. We have generated a C. elegans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…In this approach, two parts of a fluorescent protein (e.g., GFP) are fused to α-synuclein such that they will only emit fluorescence if two molecules of α-synuclein interact thereby bringing the two parts of the fluorescent protein close enough together to act as one protein [ 130 ]. In order to detect neuron-to-neuron transfer of α-synuclein, the two different BiFC-α-synuclein fusion proteins were expressed in separate populations of neurons, which are synaptically connected [ 131 ]. The observation of fluorescence in these worms indicated that the BiFC-α-synuclein molecules move from one cell to another.…”
Section: Recent Advances In Parkinson’s Disease Research In mentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, two parts of a fluorescent protein (e.g., GFP) are fused to α-synuclein such that they will only emit fluorescence if two molecules of α-synuclein interact thereby bringing the two parts of the fluorescent protein close enough together to act as one protein [ 130 ]. In order to detect neuron-to-neuron transfer of α-synuclein, the two different BiFC-α-synuclein fusion proteins were expressed in separate populations of neurons, which are synaptically connected [ 131 ]. The observation of fluorescence in these worms indicated that the BiFC-α-synuclein molecules move from one cell to another.…”
Section: Recent Advances In Parkinson’s Disease Research In mentioning
confidence: 99%
“…Having shown that neuron-to-neuron transfer occurs in C. elegans , this model can now be used to screen for modifiers of α-synuclein transfer. As a proof of principle, it was shown that genes involved in autophagy, endocytosis and exocytosis all modulate α-synuclein transfer [ 131 ]. Interestingly, silencing C. elegans orthologs of PD-related genes PRKN, PINK1, DJ-1, ATP13A2, VPS-35 , and LRRK2 using RNAi increased α-synuclein accumulation in these animals [ 131 ].…”
Section: Recent Advances In Parkinson’s Disease Research In mentioning
confidence: 99%
“…Using such models for investigation, dopaminergic neuron cell loss has frequently been reported (Chen and Feany 2005; Haywood and Staveley 2006; Park and Lee 2006; Kontopoulos et al 2006; Periquet et al 2007), although the effects appeared to be quite modest. The nematode C. elegans has also been used to demonstrate that α-syn aggregates do not only spread from neuron to neuron but are also very toxic to dopaminergic neuronal cells and can cause motor deficits in these models (Petrucelli et al 2002; Lakso et al 2003; Kuwahara et al 2006; Tyson et al 2017). Using transgenic technology and viral vector delivery approaches, rodent and non-human primate mutant α-syn-induced aggregation models have also been generated.…”
Section: Does the Aggregation And Propagation Of α-Syn Correlate Withmentioning
confidence: 99%
“…Parkinson's disease (PD) is a neurodegenerative disorder characterized by the presence of Lewy bodies (LB) and Lewy neurites (LN), which contain the presynaptic protein alphasynuclein (α-Syn, 140 residues, ~14 kD) (Spillantini et al 1997). Several factors point to α-Syn as an important player in the onset of PD: (i) six known point mutations in the α-Syn gene (SNCA) are associated with familial forms of synucleinopathies (A30P (Kruger et al 1998); A53T (Polymeropoulos et al 1997); E46K (Zarranz et al 2004); H50Q (Appel-Cresswell et al 2013); G51D (Lesage et al 2013); A53E (Pasanen et al 2014)); (ii) animal 40 models suggest a role of α-Syn in the etiology of PD, Dementia with Lewy Bodies (DLB) and Multiple System Atrophy (MSA) (Feany and Bender 2000;Hashimoto, Rockenstein, and Masliah 2003;Periquet et al 2007;Tyson et al 2017); (iii) individuals with duplications or triplications of the α-Syn gene exhibit overexpression of α-Syn and develop PD (Singleton et al 2003;Ibanez et al 2004).…”
Section: Introductionmentioning
confidence: 99%